EVALUASI KONDISI FISIK TIM BOLA VOLI JAWA TIMUR 2016 - ARDYAN, HAFES; SUBAGIO, IRMANTARA (Jurnal Prestasi Olahraga, 2019)
ABSTRACT EVALUATION OF PHYSICAL CONDITION EAST JAVA VOLLEY BALL MEN?S TEAM IN MULTI EVENT NATONAL SPORT CHAMPIONSHIP 2016 Name : Hafes Ardyan Register Number : 13060474120 Department : Education Of Sport Coaching Faculty : Faculty Of Sport Science Institution : State University Of Surabaya Advisor : Dr. Irmantara Subagio, M.Kes The Purpose of the study is to datermine the level of physical condition of men?s volleyball athletes of east java in Multi Event National Sport Championship 2016. From the test result, then will evaluation and know. The components of the physical condition under study include : speed,explosive power,flexibility,heart lunge resistance,abdominal muscle endurance. The type of the research is quantitive descriptive research. The reasearch method used survey method with testing and measurements technique. Subject in this study were athletes of men?s volleyball athletes of east java in Multi Event National Sport Championship 2016. Instrument used consisted of 5 items test. Which is a speed test 20 meter run, explosive power,flexibility,heart lunge resistance,abdominal muscle endurance. Data evaluation using quantitive descriptive statistic which poured in the form of percentage. Here are the average speed is 3,00 second and is in the moderate category, explosive power is average 1688,33 watts and is in the moderate category, flexibility is average 20,1 cm and is in the moderate category, arm muscle endurance obtained an average 9,083 repetition and are in the moderate category. And from the results evaluation analysis with calculation the average value of physical condition of east java men?s volleyball team is 65 and is in the moderate category. Keyword : Volleyball, Physical Condition, East java men?s Volleyball Athlete. ABSTRAK EVALUASI KONDISI FISIK TIM BOLA VOLI JAWA TIMUR 2016 Nama : Hafes Ardyan Nomor Pendaftaran : 13060474120 Jurusan : Pendidikan Pelatihan Olahraga Fakultas : Fakultas Ilmu Olahraga Lembaga : Universitas Negeri Surabaya Pembimbing : Dr. Irmantara Subagio, M.Kes Tujuan dari penelitian ini adalah untuk mengetahui tingkat kondisi fisik atlet bola voli putra Jawa Timur di Pekan Olahraga Nasional 2016. Dari hasil tes, maka akan dievaluasi dan diketahui. Komponen-komponen kondisi fisik yang diteliti meliputi: kecepatan, daya ledak, kelenturan, resistensi daya tahan paru, daya tahan otot perut. Jenis penelitian ini adalah penelitian deskriptif kuantitatif. Metode penelitian menggunakan metode survei dengan teknik pengujian dan pengukuran. Subyek dalam penelitian ini adalah atlet atlet bola voli putra jawa timur di Pekan Olahraga Nasional tahun 2016. Instrumen yang digunakan terdiri dari 5 item tes. Yaitu tes kecepatan lari 20 meter, daya ledak, kelenturan, multi fitness tes, daya tahan otot perut. Evaluasi data menggunakan statistik deskriptif kuantitatif yang dituangkan dalam bentuk persentase. Berikut adalah kecepatan rata-rata 3,00 detik dan dalam kategori sedang, daya ledak rata-rata 1688,33 watt dan dalam kategori sedang, fleksibilitas rata-rata 20,1 cm dan dalam kategori sedang, daya tahan otot lengan yang diperoleh rata-rata 9.083 pengulangan dan berada dalam kategori sedang. Dan dari hasil analisis evaluasi dengan perhitungan nilai rata-rata kondisi fisik tim voli putra Jawa Timur adalah 65 dan berada pada kategori sedang. Kata Kunci: Voli, Kondisi Fisik, Atlet Voli Putra Jawa Timur.